An assignment based on data driven journalism: a case study - Vanessa Simonite (Association for Learning Development in Higher Education (ALDinHE), 2012)
In a module designed to develop skills in presenting and evaluating statistics, students of mathematics and statistics were given an assignment asking them to research and write a piece of data driven journalism. Data driven journalism is a new phenomenon which has expanded rapidly due to the growth in open data, new visualisation tools and online reporting in newspapers, periodicals and blogs. The assignment provided students with a writing assignment that was individual, small-scale, research-based and embedded within their discipline.